Know all about : reduce, reuse, recycle - Nongpluh, Yoofisaca Syngkon; Noronha, Guy C.; Energy and Resources Institute (New Delhi : The Energy and Resource Institute, 2013)
Know All About: Reduce Reuse Recycle is a fresh attempt to engage you in a global problem. The book is informative and meant to help lay persons to come to grips with an all too familiar phenomenon - garbage. The book traces the history of waste and its generation - from the earliest civilizations till today - and the various efforts to find solutions. It is no technical treatise but told in a simple way. It has information, guidelines and tips on how you can help to reduce the problem that at times seems to be overwhelming us. Know All About: Reduce Reuse Recycle is, hopefully, a signpost for you along the way to cleaning up our beautiful planet and keeping it so.--COVER.
Includes bibliographical references (p. 138-140)
Keywords: Recycling (Waste, etc.) -- India; Waste minimization -- India